2011
DOI: 10.1007/s11538-010-9612-6
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of Large-Scale Movement Models in Ecology

Abstract: A difficulty in using diffusion models to predict large scale animal population dispersal is that individuals move differently based on local information (as opposed to gradients) in differing habitat types. This can be accommodated by using ecological diffusion. However, real environments are often spatially complex, limiting application of a direct approach. Homogenization for partial differential equations has long been applied to Fickian diffusion (in which average individual movement is organized along gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 26 publications
0
107
0
Order By: Relevance
“…The persistence conditions for our model differ from the ones found by Cantrell and Cosner (1999) only by a factor of D or D 1/2 , depending on k. Hence, the results with respect to a are robust across model implementations, and we conjecture that there is some deeper mathematical connection between the two approaches than first meets the eye. In particular, the derivation of skew Brownian motion might depend on using Fickian flux or biological diffusion in reaction-diffusion models (Turchin 1998;Garlick et al 2011).…”
Section: How General Are These Results?mentioning
confidence: 99%
“…The persistence conditions for our model differ from the ones found by Cantrell and Cosner (1999) only by a factor of D or D 1/2 , depending on k. Hence, the results with respect to a are robust across model implementations, and we conjecture that there is some deeper mathematical connection between the two approaches than first meets the eye. In particular, the derivation of skew Brownian motion might depend on using Fickian flux or biological diffusion in reaction-diffusion models (Turchin 1998;Garlick et al 2011).…”
Section: How General Are These Results?mentioning
confidence: 99%
“…One would expect step sizes in the random walks that dispersers follow, and therefore their diffusions rates, to vary strongly with habitat type. Recent advances in the use of homogenization [33] make integration of reaction-diffusion models with highly variable constants surprisingly easy, so building SDKs with variable diffusion and applying asymptotic techniques like homogenization will be our future concentration of research. 1 1 , n n n n j j j j t t P P S S P S t t…”
Section: Discussionmentioning
confidence: 99%
“…To estimate R 0 we refer to [24], who determined that only 6 pinyon survived the nineteenth-century fire on their site. The number of pinyon pines increased to 1051 over the next 145 years giving R 0 = 2.04/generation for pinyon from equation (33). [7] observed that Clark's Nutcracker fly from 4000 to 5000 meters while caching seeds, taking 15 -30 minutes.…”
Section: Migration Potential Of Pinyon and Junipermentioning
confidence: 99%
See 1 more Smart Citation
“…The formal mathematical description of animal movement is quite old, dating back hundreds of years, and even though the seminal text on the topic written by Turchin [47] is quite relevant, it is currently out of print and lacks a contemporary statistical perspective. Despite the existence of highly technical literature describing ways to model animal movement (e.g., [7,15]), most applied studies that have actual management or conservation objectives have sought to focus more on what is termed ''space use'', in which they seek to characterize the geographical and/or environmental space used by either individual animals or populations or both.…”
Section: Introductionmentioning
confidence: 99%